Effect of biogas sparging with different membrane modules on membrane fouling in anaerobic submerged membrane bioreactor (AnSMBR) - Aslan, Mustafa; Saatci, Yusuf; Hanay, Ozge; Hasar, Halil (Springer Heidelberg, 2014)
This study focused on the effect of biogas sparging and different membrane modules such as cylinder shaped, funnel-shaped, and U-shaped on the membrane fouling behavior in a lab-scale submerged anaerobic membrane bioreactor (AnSMBR) which was operated for over 60 days. In order to investigate the membrane fouling behavior, a series of analysis such as SMP, EPS, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), particle size distribution, and filtration resistances were performed. Although the rapid generation of cake layer took placed in case of the absence of biogas sparging, the membrane module design mostly influenced the membrane resistance when biogas sparging was applied. Total resistance was the highest for U-shaped module. The permeate fluxes with biogas sparging were higher about one half and two times than those without biogas sparging. Cylinder-shaped module had the lowest SMP and EPS concentrations followed by U-shaped and funnel-shaped modules under both cases with and without biogas sparging. The total resistances of all membrane modules without biogas sparging were found to be very high compared the pore blocking resistances (R-p).
Keywords: Anaerobic submerged membrane bioreactor; Membrane module type; Membrane fouling; Biogas sparging; SMP; EPS